2013
DOI: 10.1186/1479-5876-11-108
|View full text |Cite
|
Sign up to set email alerts
|

The engagement of CTLA-4 on primary melanoma cell lines induces antibody-dependent cellular cytotoxicity and TNF-α production

Abstract: BackgroundCTLA-4 (Cytotoxic T lymphocyte antigen-4) is traditionally known as a negative regulator of T cell activation. The blocking of CTLA-4 using human monoclonal antibodies, such as Ipilimumab, is currently used to relieve CTLA-4-mediated inhibition of anti-tumor immune response in metastatic melanoma. Herein, we have analyzed CTLA-4 expression and Ipilimumab reactivity on melanoma cell lines and tumor tissues from cutaneous melanoma patients. Then, we investigated whether Ipilimumab can trigger innate im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 37 publications
2
106
0
4
Order By: Relevance
“…For example, cytokines produced by activated T cells by CTLA4 blockade therapy might activate NK cells and initiate their antitumour effector functions. CTLA4 can also be expressed on some tumour cells 105 and thus induce ADCC after treatment with CTLA4 anti bodies 106 . Moreover, tumour cells infected with oncolytic viruses, such as Newcastle Disease virus 107 and H-1PV rat parvovirus 108 , have been shown to stimulate NK cells directly by inducing activating ligands on the virus-infected cells.…”
Section: Checkpoint Blockade Of Nk Cellsmentioning
confidence: 99%
“…For example, cytokines produced by activated T cells by CTLA4 blockade therapy might activate NK cells and initiate their antitumour effector functions. CTLA4 can also be expressed on some tumour cells 105 and thus induce ADCC after treatment with CTLA4 anti bodies 106 . Moreover, tumour cells infected with oncolytic viruses, such as Newcastle Disease virus 107 and H-1PV rat parvovirus 108 , have been shown to stimulate NK cells directly by inducing activating ligands on the virus-infected cells.…”
Section: Checkpoint Blockade Of Nk Cellsmentioning
confidence: 99%
“…17,24 Although the prevailing notion is that ipilimumab targets CTLA-4 on T cells, its exact mode of action is still under discussion, as CTLA-4 can be expressed on regulatory lymphocytes as well as on malignant cells. [25][26][27][28][29] In an early trial investigating the CLTA-4 antibody tremelimumab in metastatic gastric adenocarcinoma, tumor shrinkage with some long-lasting responses have been described. Of note, this study did not report on CTLA-4 expression on primary tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies indicated that CTLA-4 expression in tumour cells is associated with poor prognosis (12,17). CTLA-4 engagement with B7 ligands induces tumour cell death through apoptosis (18), and ipilimumab triggers effector lymphocytes and tumour necrosis factor release to directly eliminate CTLA-4 + melanomas (14). These studies have indicated the potential function of CTLA-4 in tumour cells.…”
Section: Introductionmentioning
confidence: 99%
“…CTLA-4 has also been implicated to serve functions in neoplastic cells, including B cell chronic lymphocytic leukaemia (10), non-Hodgkin's lymphoma (11), breast cancer (12), lung cancer (13), melanoma (14), gastric cancer (15), colorectal cancer (15), cervical cancer (16) and oesophageal carcinoma (17). Prior studies indicated that CTLA-4 expression in tumour cells is associated with poor prognosis (12,17).…”
Section: Introductionmentioning
confidence: 99%